A Comparison of the Double-Half Bilobe Flap to the Traditional Bilobe Flap: Cohort Analysis of a Single Surgeon Experience - Baird, Brandon J.; Moubayed, Sami P.; Most, Sam P. (Facial Plastic Surgery, 2017)
The double-half bilobe flap was initially described by the senior author (S.P.M.) in 2012 to address defects of the midline nasal tip typically after ablative carcinoma resection. It is a unique reconstructive option for the nasal tip, as it does not depend on a unilateral tissue advancement vector, instead using bilateral and opposing vectors to maintain symmetry. In this retrospective cohort series, we evaluated patient- and physician-derived outcomes and baseline characteristics from a group of 17 patients that underwent reconstruction with the double-half bilobe flap. A control group of 65 patients that underwent traditional bilobe reconstruction for defects of one nasal subunit (tip, side wall, or dorsum) was used for comparison. Outcome measures included infection, symmetry, pin-cushioning, scarring, reoperation, and adjunct procedures. Also, patient satisfaction was evaluated by using frequency of follow-up as a surrogate for patient discontentment with aesthetic outcome. The double-half bilobe flap provides improved symmetry and otherwise similar overall outcomes compared with the traditional bilobe flap, and should be considered as a primary option for the reconstruction of midline nasal tip defects less than 15 mm in diameter.
Keywords: bilobe flap; skin cancer; reconstruction; local flap